Mycophagous rove beetles highlight diverse mushrooms in the Cretaceous - Chenyang Cai (Nature Portfolio, 2017)
Agarics (gilled mushrooms) are rarely preserved as fossils, which has obscured their evolutionary history. Here, the authors describe new forms of agarics as well as new species of rove beetles with morphological specializations for mushroom feeding discovered in 99-million-year-old Burmese amber.